Blockchain-based handle-research data sharing: a blockchain-based handle system to enhance the privacy and security of research data sharing - Hisseine, Mahamat Ali; Chen, Deji; Xiao, Yang (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
The increasing demand for secure, persistent and interoperable research data (RD) sharing makes traditional systems vulnerable. All research objects should be findable, accessible, interoperable and reusable (FAIR) for machines and people. This paper proposes a novel framework called blockchain-based handle- RD sharing (BHRDS), which integrates the handle system for persistent identifiers (PIDs) with a smart contract for access control and mirror-specific encryption, BLAKE2-based hashing for identity binding and irregularity detection. The system utilizes swarm, a decentralized storage layer, for off-chain data storage while storing only credential metadata and access conditions on-chain. The framework enables secure identity data management, and verifiable credential distribution across multiple mirror sites. We conducted experiments under growing user numbers (10 to 10,000), different encryption key strengths (AES 128, 192, and 256 bits), and blockchain load conditions. Results show that BHRDS achieves high irregularity detection rates (above 97%) and maintains low response times even at scale. In all the test instances, the system performed accurately, demonstrating that BHRDS offers a decentralized data access model that is scalable and aligned with the FAIR principle, making it suitable for next-generation scientific and institutional data sharing.